Psychometric properties and reliability of the Assessment Screen to Identify Survivors Toolkit for Gender Based Violence (ASIST-GBV): results from humanitarian settings in Ethiopia and Colombia - Vu, Alexander (Confl Health, 2016)
BACKGROUND: Refugees and internally displaced persons who are affected by armed-conflict are at increased vulnerability to some forms of sexual violence or other types of gender-based violence. A validated, brief and easy-to-administer screening tool will help service providers identify GBV survivors and refer them to appropriate GBV services. To date, no such GBV screening tool exists. We developed the 7-item ASIST-GBV screening tool from qualitative research that included individual interviews and focus groups with GBV refugee and IDP survivors. This study presents the psychometric properties of the ASIST-GBV with female refugees living in Ethiopia and IDPs in Colombia. METHODS: Several strategies were used to validate ASIST-GBV, including a 3 month implementation to validate the brief screening tool with women/girls seeking health services, aged ≥15 years in Ethiopia (N = 487) and female IDPs aged ≥ 18 years in Colombia (N = 511). RESULTS: High proportions of women screened positive for past-year GBV according to the ASIST-GBV: 50.6 % in Ethiopia and 63.4 % in Colombia. The factor analysis identified a single dimension, meaning that all items loaded on the single factor. Cronbach’s α = 0.77. A 2-parameter logistic IRT model was used for estimating the precision and discriminating power of each item. Item difficulty varied across the continuum of GBV experiences in the following order (lowest to highest): threats of violence (0.690), physical violence (1.28), forced sex (2.49), coercive sex for survival (2.25), forced marriage (3.51), and forced pregnancy (6.33). Discrimination results showed that forced pregnancy was the item with the strongest ability to discriminate between different levels of GBV. Physical violence and forced sex also have higher levels of discrimination with threats of violence discriminating among women at the low end of the GBV continuum and coercive sex for survival among women at the mid-range of the continuum. CONCLUSION: The findings demonstrate that the ASIST-GBV has strong psychometric properties and good reliability. The tool can be used to screen and identify female GBV survivors confidentially and efficiently among IDPs in Colombia and refugees in Ethiopia. Early identification of GBV survivors can enable safety planning, early referral for treatment, and psychosocial support to prevent long-term harmful consequence of GBV.